Shaped beam synthesis of concentric ring array antenna using Differential Evolution Algorithm - Mandal, D.; Chatterjee, A.; Mondal, T.; Bhattacharjee, A.K. (International journal of electronics and communications, 2015)
A shaped beam synthesis from a concentric ring array has been presented. Two different cases are considered. In the first case, a flat-top beam with desired specification has been generated and in the second case, a cosec2 beam pattern from the same array configuration is generated. The desired beam pattern in each of the individual case is obtained by finding optimum excitations of the array elements using Differential Evolution (DE) algorithm. Dynamic range ratio (DRR) of the excitation amplitudes are improved by eliminating the weakly excited array elements from the optimized array without distorting the obtained pattern. To illustrate the effectiveness of DE, the two beam-patterns are computed from the same array using Genetic Algorithm (GA) by finding out optimum excitations among the elements. Results clearly show the superiority of DE over GA to handle the proposed problem.